THE EFFECTS OF SERVICE QUALITY, AND CUSTOMER SATISFACTION TOWARDS BUS TICKET PRICES OF PT. CHANDRA - Safrida (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The purpose of this study was to determine the effect of service quality and price on ticket purchasing decisions at PT. Chandra Medan. The technique used in sampling is accidental sampling with a total of 50 respondents. Sources of data using primary data in the form of questionnaires/questions and secondary data obtained from literature, documents and the internet. The data was processed using SPSS version 21. The data analysis technique used was multiple linear regression with the formula Y = a + b1 X1 + b2 X2 + e and to find out how much influence service quality and price have on purchasing decisions for passenger tickets on PT. Chandra Medan uses a comparison technique t test and F test. The results of the validity test and reliability test of the questionnaire, each question item is declared valid and reliable where if the value of Rcount> Rtable with the value of all items is above the value of 0.729 and the regression equation Y = 4.253 + 0.178X1 + 0.375X2 means that every increase by one unit will cause an increase in customer satisfaction by 0.178 and 0.375. To know whether the hypothesis in this study is accepted or not, the t-count test technique is used. Fcount obtained tcount value of service quality of 2.331 and tcount price value of 3.603 and ttable 2.012 and obtained Fcount value of 15.988, while Ftable 3.90 and and the level of significance (0.000 <0.005) indicates that service quality (X1) and price (X2) collectively have a significant effect on purchasing decisions.